A difficult bite: An overview of dysphagia - Mignini, Elsa Veronica; Catani, Milena; Ferrara, Marco; Taus, Marina (Progress in Nutrition, 2024)
Dysphagia describes the difficulty in swallowing during the passage of a bolus from the mouth to the stomach or the perception of obstruction during swallowing. It is a symptom of several oncological, neurological or neuromuscular pathologies. Dysphagia can also be found in sarcopenic patients, as a clinical feature of loss of strength and function of swallowing muscles. Diagnosis can be challenging due to the non-specificity of symptoms and the heterogeneity of aetiology and requires a multidimensional approach, comprising screening tools and instrumental assessment. Dysphagia is an issue of nutritional interest since predisposes to malnutrition and dehydration. Dysphagic patients, indeed, are usually not able to cover their nutritional and fluid needs both because of the change in swallowing mechanics and because the nutritional value of texture-modified diets. A well-structured nutrition plan needs a multidimensional approach developed by a multidisciplinary tea, who firstly define the nutritional needs, work on the adequate nutritional plan, then predispose a well-organized follow-up. Food fortification, in-between-meal nutritious snacks and oral nutritional supplements, artificial nutrition, preferably enteral nutrition through nasogastric tube or gastrostomy are the essential steps of nutritional management of dysphagic patients.